Border sexuality: identity experiences and inclusion paths of women with non-heteronormative sexual orientation born from mixed couples - Masullo, Giuseppe; Ferrara, Carmela (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2020)
The article examines the processes of identification of women born from mixed couples (one Italian and one foreign parent), to explain the complexity in the self-determination processes of women with nonhetero-normative sexuality living in multicultural families. Based on the intersectionality paradigm, we will analyse how biosocial categories such as sex, gender, sexual orientation, class, name, skin colour, family background may influence the self-definition identity processes and generate multiple discrimination. Inspired by Gloria Anzaldúa’s thoughts, we will highlight how girls shun widespread heteronormative models not only of mainstream society, but of the LGBT community itself. We also applied a methodology used in non-formal education, which allowed us to explore how the women interviewed put different aspects of themselves to the test, negotiating them in the different scenarios of everyday life, in an attempt to counteract situations for which they can feel stigmatized and oppressed.